The Effect of the Scientific Approach Assisted by Animated Videos on Conceptual Understanding in Ecosystem Material in Class X MAS YPRA Batang Kuis - Mariska Maujana Siregar mariska; Syarifah Widya Ulfa; Rohani (Bioeduca : Journal of Biology Education, 2026)
The study conducted at MAS YPRA Batang Kuis aimed to examine the effectiveness of a scientific learning model assisted by animated videos compared to a traditional learning model. The research involved Grade 10 students at MAS YPRA Batang Kuis, located in Batang Kuis District, Deli Serdang Regency. A total of 64 students participated, with Class X Science 1 assigned as the experimental class and Class X Science 2 as the control class. Data analysis showed that the experimental class obtained a pretest score of 930 and a posttest score of 2416, with an increase of 67.76% in the good category. The control class obtained a pretest score of 800 and a posttest score of 2110, with an increase of 62.08%, also in the good category. Hypothesis testing concluded that Ho was accepted and Ha rejected, indicating a significant difference between the two learning models. Students taught using the animated video-assisted scientific model demonstrated better conceptual understanding than those taught using the traditional learning model.